Effects on Outpatient and Emergency Mental Health Care of Strict Medicaid Early Periodic Screening, Diagnosis, and Treatment Enforcement - Snowden, Lonnie R. (American Public Health Association, 2007)
We investigated enforcement of mental health benefits provided by California Medicaid’s Early Periodic Screening, Diagnosis, and Treatment (EPSDT) program. Enforcement, compelled by a consumer-driven lawsuit, resulted in an almost 4-fold funding increase over a 5-year period. We evaluated the impact of enforcement on outpatient treatment intensity (number of visits per child) and rates of emergency care treatment. Using fixed-effects regression, we examined the number of outpatient mental health visits per client and the percentage of all clients using crisis care across 53 autonomous California county mental health plans over 32 three-month periods (quarters; emergency crisis care rates) and 36 quarters (out-patient mental health visits). Enforcement of EPSDT benefits in accordance with federal law produced favorable changes in patterns of mental health service use, consistent with policy aims.